Strengthening Religious Character at SMK Plus Nurul Hakim - Ayyub; Faridi; Nurhakim (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2024)
SMK Plus Nurul Hakim implements religious character strengthening through various routine activities arranged in structured programs. This research uses a qualitative approach with the type of field research to explain the implementation of religious character strengthening in the school. The results showed that: 1) The foundation of strengthening students' religious character is the school's vision and mission; 2) Activities that support the strengthening of religious character include: dhuha prayer, sunnah rawatib prayer, Monday-Thursday and Arofah fasting, kultum and muhadhoroh, environmental care, and social service; 3) The religious character strengthening program at SMK Plus Nurul Hakim includes the habituation of sunnah worship, the amar ma'ruf nahi mungkar program, and the Uswah and Qudwah program (imitating and modeling).